Role of identity in the business ecosystem: an inquiry in Indian stone carving clusters. Issue 4 (2nd September 2019) - Panda, Debadutta Kumar
Abstract : Purpose: The purpose of this study is to understand the business ecosystem through the "identity" construct. "Identity" is a well-researched subject in sociology and psychology but as a construct, its application is limited in management and organization studies, especially in the ecosystem context. This study used "identity" to examine the management and organization of stone carving microenterprise clusters in India. Design/methodology/approach: The examination followed classical grounded theory approach for data collection and data analysis. Data collection was made by a mixture of focus group discussions, informal discussions, personal observations, etc., and it followed a series of thematic analysis under the qualitative technique. Further, a structured questionnaire was used to collect information, and the data analysis was done through structural equation modelling and confirmatory factor analysis. Findings: The study identified and established ten identities of the producers, two identities of the suppliers and two identities of the customers. There were identity-interlinkages within each stakeholder, and among the stakeholders, creating a solid, static and rigid ecosystem for ages. Originality/value: This paper made a new and significant contribution to the literature on the business ecosystem.